The Influence of Religiosity and Self-Esteem on Life Purpose through Peer Support - Diky Arya Prakosa; Heru Mugiarso; Ernest Ceti Septyanti (Universitas Negeri Semarang, 2025)
Generation Z faces a variety of psychological and social challenges that impact the development of life goals, including academic pressure, social comparison through digital media, and increased anxiety and symptoms of mental illness. Consequently, many students experience confusion about their life direction, and some even begin to exhibit risky behaviors in response to these pressures. Gen Z, as digital natives , faces mental health challenges and the need for a clear sense of purpose during their critical years at university. This study used quantitative research with a survey of 332 psychology students from three universities, applying validity and path analysis tests to investigate the relationships between variables. This study aims to analyze the influence of religiosity and self-esteem on the life goals of Gen Z college students in Surakarta, with peer support as a mediating variable. The results can serve as a basis for developing more effective college guidance and counseling services that balance religiosity, self-esteem, and social support. The results of this study can be a theoretical contribution to the study of student development and help educational institutions in designing relevant intervention programs to address psychological problems and future orientation of students.